Gandhian engagement with capital :perspectives of J.C. Kumarappa - Chaitra Redkar (Sage, 2019)
Gandhian Engagement with Capital: Perspectives of J C Kumarappa comprehensively presents the Gandhian ideas on economic development and political economy.